Does decentralised governance of primary education improve performance of pupils in Eastern Uganda? – Perspectives of education managers - Namara, Rose B. (Commonwealth Journal of Local Governance, 2020)
This study seeks to establish the role decentralised governance has played in the performance of primary schools in eastern Uganda. Exploratory and descriptive data drawn from 104 school managers and district officials participating in the study indicate that decentralised governance has strengthened management of the payroll, increased regularity of monitoring and supervision and introduced school management committees. Despite these improvements in governance, there is however evidence that the quality of primary education continues to be low. Only a small and declining percentage of pupils complete primary education, and with increasingly poor grades. This is because, for a number of reasons, both the supply and demand side of governance are still weak. Despite this, overall the author finds that decentralised governance of primary education is a positive development, as it has enhanced the supply side of governance. There is, however, a need to control negative practices in the supply side of governance, and to systematically develop the demand side of governance, if the performance of Ugandan pupils is to improve.
Keywords: Primary education; decentralisation; governance; pupil performance; education managers